(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2014)
Studying protein characteristics and their molecular interactions can provide an important route to investigate protein networks in living cell. It can also postulate the functions of newly discovered genes or proteins, thus, hold great value for understanding disease mechanisms9-11 and providing suitable diagnostics for the global-threatening diseases.12,13 To date, works have vastly being done in these areas (proteomics studies) in order to develop a simple noninvasive tests that can indicate disease risk at early stage.14One of the keys that plays important role in these research areas is nanobio-sensor technology. The technology provides analytical tools upon knowing the abundance, and also qualitative characterization of a particular biomolecule. Therefore, the development of biosensor technology is important, and is expected to meet the needs ofanalyzing protein behavior (interactions, activities, etc.) accurately and effectively.